Thiol dependent isomerization of all- trans-retinoic acid to 9- cis-retinoic acid - Urbach, Jonathan; Rando, Robert R. (FEBS letters, 1994)
The important biological effector 9- cis-retinoic acid can be generated by liver microsomes or by bovine serum albumin in detergent. The mechanism of this isomerization reaction is the subject of these studies. The protein mediated isomerization process is shown to be thiol- and pH-dependent. Moreover, the retinoic acids are also isomerized by 1-dodecanethiol in the presence of detergents. This isomerization process is pH-dependent as well, with isomerization rates increasing with pH. The isomerization reactions are quenched with free radical traps, such as α-tocopherol and ascorbic acid, suggesting that a thiol radical mechanism, rather than a thiolate anion-dependent mechanism, is implicated here. The pH dependence can be understood in terms of a thiol radical mechanism, because thiol radicals are produced from thiolate anions in the presence of oxygen. The facile thiol-mediated isomerization of the retinoic acids suggests that this could be a physiologically relevant mechanism for the formation of 9- cis-retinoic acid from all- trans-retinoic acid.